Entrapment of Lipase from Candida antarctica in a Xerogel for the Production of Biodiesel from Waste Cooking Oil - Decarpigny, Cédric; Bigan, Muriel; Froidevaux, Rénato (ChemBioChem, 2025)
International audience The process to synthesize biodiesel is well-developed and optimized to overcome the disadvantages like the competition with agriculture using feedstock, and the problematics in the process. Oils from waste and enzymatic catalysis have proven to be good solutions to these problems. Lipases are currently the most commonly used enzymes in the transesterification of oils; nevertheless, enzymes have a high cost and must be immobilized to offer repetitive reuse. This work focuses on the synthesis and the optimization of the conditions of a xerogel where the lipase from Candida antarctica is immobilized by entrapment. The xerogel synthesized here, a glass-like material, proved to be very effective in maintaining the enzyme on its structure, with an immobilization yield of 96 % and an activity of 5.3 U/mg (free lipase = 12.1 U/mg). By grinding this xerogel, the immobilization yield remained constant (94 %). Nevertheless, grinding the xerogel allowed better diffusion of reagents, and the activity reached 9.7 U/mg. Using this xerogel in biodiesel production had a positive effect on CALB efficiency by increasing the biodiesel yield, 46.1 % against 15.1 % with free CALB. Finally, the catalyst could be reused for five runs without loss of activity.